2007
DOI: 10.1007/978-3-540-73281-5_74
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Virtual Reality Games for Rehabilitation of Motor Disorders

Abstract: This paper describes the development of a Virtual Reality (VR) based therapeutic training system aimed at encourage stroke patients with upper limb motor disorders to practice physical exercises. The system contains a series of physically-based VR games. Physically-based simulation provides realistic motion of virtual objects by modelling the behaviour of virtual objects and their responses to external force and torque based on physics laws. We present opportunities for applying physics simulation techniques i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 9 publications
0
22
0
4
Order By: Relevance
“…Many studies [1], [2] have identified the benefits of using serious games in movement therapy to improve balance, postural control and fine motor movement. One new mode of movement therapy may be to design and develop an innovative collection of computer games which provide an engaging, self-reinforcing context in which to practice physical activities of the upper limb in people with stroke and to achieve therapeutic goals [3]. This paper details the development and testing of a seriousgame based movement therapy aimed at encouraging stroke patients with upper limb motor disorders to practice physical exercises and therefore enhance endurance, dexterity, speed and range of motion.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies [1], [2] have identified the benefits of using serious games in movement therapy to improve balance, postural control and fine motor movement. One new mode of movement therapy may be to design and develop an innovative collection of computer games which provide an engaging, self-reinforcing context in which to practice physical activities of the upper limb in people with stroke and to achieve therapeutic goals [3]. This paper details the development and testing of a seriousgame based movement therapy aimed at encouraging stroke patients with upper limb motor disorders to practice physical exercises and therefore enhance endurance, dexterity, speed and range of motion.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as gravity can be scaled to adapt to individual patient's abilities and in-game performance" (Ma et al, 2007).…”
Section: Adaptation Within Rehabilitation Vr Gamesmentioning
confidence: 99%
“…(Yamashita, 2014). ( Pirovano et al, 2012), (Ijsselsteijn et al, 2007), (Ma. 2007), (Kizony,2003) (EU iStoppFalls) (Myers et al, 2000).…”
Section: Summary Of Technologies Used Within Virtual Training Simulatorsmentioning
confidence: 99%
“…Ma [18] developed an adaptive VR game for post-stroke patients with upper extremity deficiencies that aim to encourage movement and improve their accuracy and speed. The game can be controlled through motion data captured by three sensors, Motion-Star Wireless, VR 1289 HMD, and the 5DT data glove that enable the detection of the position and orientation of the patient's hand.…”
Section: Related Literaturementioning
confidence: 99%